The Usage of Critical Thinking Technology in Educational Process - Rakhimdjanova Malikakhon (Genius Journals, 2022)
As we know, critical thinking is the ability to ask questions, develop a variety of arguments, and make independent, thoughtful decisions. Therefore, the main idea of using technology for me is to create such an atmosphere of learning through playful methods, in which students, together with the teacher, actively communicate, consciously reflect on the learning process, track, confirm, refute or expand knowledge, new ideas, feelings or opinions about the world around them. And, of course, they do it quite fluently in English. In this article, we tried to systematize our and colleagues experience in the use of critical thinking techniques in modern English lessons.
Keywords: Critical Thinking; Reading; Writing; Information